Anterior cruciate ligament injury prevention in female lacrosse players based on an examination of knee and hip joint mechanics during drop vertical jumps performed while holding a lacrosse stick - Sanomura, M.; Fukubayashi, T. (Sports injuries and prevention, 2015)
Anterior cruciate ligament (ACL) injuries occur during jumping and cutting maneuvers. Female lacrosse is associated with a higher incidence rate of ACL injuries than other female sports. Video analysis of ACL injuries has shown that the valgus knee angle is larger in injured athletes compared with controls, and the knee flexion angle tends to be smaller. In recent years, there has been focus on dynamic lower limb alignment, and the drop vertical jump (DVJ) task has been recommended as a method for assessing the risk of injuries to knee ligaments such as the ACL. The purpose of this study was to examine knee and hip joint mechanics during performance of the DVJ task while holding a lacrosse stick. Nine female collegiate lacrosse players participated in this study. Thirty-six reflective markers were placed on the upper limbs, trunk, pelvis, and right lower limb. An eight camera motion analysis system in conjunction with a force plate were used to record the three-dimensional marker positions and ground reaction forces. Three drop jump tasks were performed while not holding a lacrosse stick (NH), holding a lacrosse stick in the right hand (RH), and holding a lacrosse stick in the right hand with a target ball (RHT). The peak values of knee flexion and abduction angle, hip flexion and adduction angle, knee abduction and hip adduction moment from initial contact to 30 % phase in the landing phase were analyzed. Peak knee flexion angle in the RHT condition was significantly smaller than that in the RH condition (109.7±10.4 vs. 113.5°±?9.8°, p<0.05). The results of this study suggest that when screening to prevent ACL injury in female lacrosse players, the DVJ task while holding a stick and a target may be a useful means of examining the risk of lower limb injury such as an ACL tear. Additionally, when teaching movements to prevent ACL injury, it is important to emphasize landing from a jump with the knees deeply bent.